Delayed immunologic thrombocytopenia induced by abciximab - Nurden, Paquita; Clofent-Sanchez, Gisèle; Jais, Catherine; Bermejo, Emilse; Leroux, Lionel; Coste, Pierre; Nurden, Alan T. (Thrombosis and Haemostasis, 2004)
Abciximab is an anti-GPIIb-IIIa drug widely used to prevent thrombotic complications during percutaneous coronary intervention. We now report on the immunologic origin of thrombocytopenia developing between 7 and 12 days after the onset of abciximab infusion. Antibodies directed against abciximabcoated platelets were located in 5 patients with delayed thrombocytopenia, just as they were present in a patient whose platelet count fell within a few hours after receiving the drug. Abciximab-dependent IgG antibody was revealed in serum using control platelets in the monoclonal antibody immobilization of platelet antigens assay (MAIPA) performed with SZ22, a MoAb to GPIIb. The presence of IgG antibodies specific for platelets sensitized with abciximab was confirmed by flow cytometry. They were not located in 13 patients receiving abciximab but whose platelet counts remained stable. For three patients, antibodies were transient and their presence related to the extent of the thrombocytopenia. Surprisingly, antibodycontaining plasma from three patients induced abciximabdependent activation and aggregation of normal platelets, a finding confirmed by electron microscopy. Immunogold labeling revealed that abciximab was associated with platelets in the aggregate, suggesting that its inhibitory effect was overcome by the platelet stimulation. In summary, these results show that abciximab-dependent thrombocytopenia can be delayed and potentially prothrombotic.
Keywords: Abciximab; percutaneous coronary intervention; delayed thrombocytopenia; thrombotic risk